Rom, Italien: Urbs sacra. Sakrale Sphären des kaiserzeitlichen Rom - Neudecker, Richard (e-Forschungsberichte des DAI, 2023)
The sacral topography of Rome in Imperial Times is thoroughly reconstructed, documented and interpreted. On the basis of archaeological, literary and epigraphic evidence appr. 500 sacral points, monuments, areas and zones could be identified so far, which will now be interpreted and analyzed.